Strengthening Character Education for Elementary School Students in School Settings - Widya Trio Pangestu; Degi Alrinda Agustina (Universitas Trunojoyo Madura, 2022)
Character education is important to be implemented in students as early as possible and on an ongoing basis. School is a strategic place for character education because children from all walks of life will receive education at school. In addition, children spend most of their time at school, so what they get at school will affect the formation of their character. Therefore, character education must be applied to all levels of formal education, but a larger portion must be given to the elementary school level compared to other levels of education. This is because elementary school students are still not contaminated by bad qualities, so it is very possible to instill the noble character or character of our nation which will eventually stick in the souls of children until they grow up. In the practice of character education in schools, all components must be involved, including the components of education itself, namely curriculum content, learning and assessment processes, subject handling or management, school management, implementation of extracurricular activities or activities, empowering facilities and infrastructure, financing, and the work ethic of all members of the school/environment. Each component must mutually support the implementation of proper character education, cannot stand alone and must be sustainable.